PENGARUH KEMAMPUAN MANAJERIAL DAN MOTIVASI KERJA KEPALA SEKOLAH TERHADAP KUALITAS PENERAPAN MANAJEMEN BERBASIS SEKOLAH - Astuti, Eka Yuli; Tobari, Tobari; Tahrun, Tahrun (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2021)
Managerial ability and work motivation of school principals are important for a leader to have so that the implementation of school-based management can be implemented well. This study was conducted with the aim to determine the effect of the principal's managerial ability on the quality of school-based management implementation, work motivation of principals on the quality of school-based management implementation and the influence of managerial ability and work motivation of principals together on the quality of school-based management implementation in high school all Makarti Jaya Districts. This research method is quantitative descriptive. The research sample used the Slovin formula and was taken by simple random sampling technique. The results of the research conducted are managerial ability has a positive and significant impact on the quality of the application of school based management.